Maximization of Seed Size Tuber Production in Early Bulking Potato (Solanum tuberosum L.) Variety Kufri Khyati - Sadawarti, Murlidhar; Singh, R. K.; Samadhiya, R. K.; Singh, S. P.; Pandey, K. K.; Roy, Satyajit; Chakrabarti, S. K. (International Journal of Bio-resource and Stress Management, 2017)
A field experiment was conducted at ICAR Central Potato Research Station Gwalior, MP, during 2015–16 and 2016–17 to study the effect of intra-row spacing, nitrogen levels and date of haulm killing on production of higher proportion of seed size tubers in early bulking variety Kufri Khyati. Treatments consisted of two intra-row spacing (15 cm and 20 cm), two dates of haulm killing (70 and 80 days) and two nitrogen levels (120 and 150 kg ha-1). Treatments were replicated three times with split plot design. Germination percentage was significantly higher in 20 cm spacing (96.76%) over 15 cm spacing (88.12%). Non-significant differences were recorded among different parameters for growth attributes. Significantly highest seed size tuber and total tuber number was recorded in 15cm spacing (405000 ha-1 and 716000 ha-1) over 20 cm spacing (337000 ha-1 and 605000 ha-1) respectively. Non-significant but highest seed size tuber number (432000 ha-1 and 427000 ha-1) was recorded in 15 cm intra-row spacing×80 days haulm killing×150 kg N and 15 cm intra - row spacing×70 days haulm killing×120 kg N respectively. Seed size and total tuber yield (t ha-1) was in significantly higher 15 cm spacing (22.44 t ha-1 and 33.16 t ha-1) over 20 cm spacing (19.81 t ha-1 and 29.84 t ha-1). Significantly higher severe mosaic incidence (0.87%) was observed with 80 days haulm killing over 70 days. Hence 15 cm intra - row spacing×70 days haulm killing×120 kg N was most suitable for getting higher proportion of seed size tubers in Kufri Khyati.